Hubungan antara Sense of Humor dengan Makna Hidup pada Remaja Putus Sekolah - Caba, Azlizan; Kurniati Zainuddin (Indonesian Journal of Islamic Counseling, 2023)
The impact of dropping out of school on adolescents is an identity crisis that can lead to meaningless or life without meaning. Adolescents who have no meaning in life will feel pessimistic and confused in determining the purpose of life. One of the factors that can affect the meaning of life is the ability to take the right attitude towards tragic events. Sense of humor is an individual's ability to view negative events with more positive thoughts. Individuals who have a good sense of humor can cope with the discrepancy between expectations and reality. This study aims to determine whether there is a relationship between sense of humor and the meaning of life in out-of-school adolescents. The research uses a survey type quantitative method. Respondents in this study consisted of 100 adolescents aged 18-22 years who had dropped out of school. The data analysis technique used to test the hypothesis is sperm rank correlation. The results of the study show that there is a significant relationship between sense of humor and the meaning of life in adolescents dropping out of school with a significance value of 0.00 and a correlation coefficient of 0.507, which means the level of strength of the relationship is quite strong. These results show that an increased sense of humor can help dropout teenagers to get a good meaning in life.